Comparison of Noninvasive Imagery Methods to Observe Healthy and Degenerated Olfactory Epithelium in Mice for the Early Diagnosis of Neurodegenerative Diseases - Etievant, Adeline; Monnin, Julie; Lihoreau, Thomas; Tamadazte, Brahim; Rougeot, Patrick; Magnin, Eloi; Tavernier, Laurent; Pazart, Lionel; Haffen, Emmanuel (Frontiers in Neuroanatomy, 2020)
Olfactory dysfunction could be an early and reliable indicator for the diagnosis of neurodegenerative disorders such as Alzheimer and Parkinson's diseases. In this paper, we compare the potential of different noninvasive medical imaging modalities (optical coherence tomography, confocal microscopy, and fluorescence endomicroscopy) to distinguish how the olfactory epithelium, both at the cellular and the structural levels, is altered. Investigation were carried out on three experimental groups: two pathological groups (mice models with deliberately altered olfactory epithelium and Alzheimer's disease transgenic mice models) were compared with healthy mice models. As histological staining, the three tested noninvasive imaging tools demonstrated the general tubular organization of the olfactory epithelium on healthy mice. Contrary to OCT, confocal microscopy and endomicroscopy allowed visualizing the inner structure of olfactory epithelium as well as its morphological or functional changes on pathological models, alterations classically observed with histological assessment. The results could lead to relevant development of imaging tools for noninvasive and early diagnosis of neurodegenerative diseases through the in situ characterization of the olfactory epithelium